Bird species diversity in Altai riparian landscapes: Wood cover plays a key role for avian abundance. Issue 17 (20th August 2019) - Li, Na; Sun, Yuehua; Chu, Hongjun; Qi, Yingjie; Zhu, Lan; Ping, Xiaoge; Li, Chunwang; Jiang, Zhigang
Abstract: Aims: We aim to understand bird richness and variation in species composition (beta diversity) along a 630 km riparian landscape in the Altai Mountains of China and to test whether vegetation cover is the main explanation of species diversity. Methods: We selected nine regions along a gradient of natural vegetation change. Bird surveys and environmental measurements were conducted at 10 points in each of the nine regions. We collected environmental land cover variables such as wood cover (area proportion of trees and shrubs with saplings in habitats; here trees are woody plant with a single trunk and higher than 3 m, shrubs and saplings are distinguished from trees by their multiple trunks and shorter height) and tree cover, and two climate factors which were Annual Mean Temperature (AMT) and Annual Precipitation (AP). We used Liner Regression Models to explore the correlation between bird species richness and environmental variables. We used Sørensen's dissimilarity index to measure birds' beta diversity, and quantified the contribution of environmental variables to this pattern using a Canonical Correspondence Analysis (CCA). Results: Wood cover was the strongest predictor of overall, insectivore, and omnivore bird richness. Regions with wood cover contained more bird species. Beta diversity was overall high in the studied regions, and turnover components occupied a major part of beta diversity. Wood cover and AP were significant predictors of bird species composition explaining 33.24% of bird beta diversity together. Conclusions: Wood vegetation including trees, shrubs, and saplings, rather than only trees, contains high bird richness. High beta diversity suggests that expansion of the existing nature reserves is needed in the riparian landscapes to capture the variation in bird species composition. Thus all wood cover in the overall riparian landscapes of Altai Mountains should be protected from farming and grazing to improve bird conservation outcomes. OPEN RESEARCH BADGES: This article has earned an Open Data Badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available at Raw bird data in this study: osf.io/78qcw ; Raw environment data: osf.io/qr5cw . Abstract : We found high bird diversity in the riparian landscapes of Altai Mountains. The area proportion of wood cover, including tall trees, shrubs, and young saplings, was the most associated factor to explain bird species richness and composition variation.